Anti-Angiogenesis Drug Discovery and Development. - Atta-ur-Rahman (Bentham Science Publishers, 2011)
The inhibition of angiogenesis is an effective mechanism of slowing down tumor growth and malignancies. The process of induction or pro-angiogenesis is highly desirable for the treatment of cardiovascular diseases, wound healing disorders, etc. Efforts to understand the molecular basis, both for inhibition and induction, have yielded fascinating results. Anti-angiogenesis Drug Discovery and Development provides an excellent compilation of well-written reviews on various aspects of the anti-angiogenesis process. These reviews have been contributed by leading practitioners in drug discovery scien.